Pengaruh Kelebihan Muatan Kendaraan (Overload) Terhadap Konstruksi Perkerasan Jalan Raya Pada Ruas Jalan Mahir-Mahar Kota Palangka Raya - Ipana Novela; Robby Robby; Salonten Salonten (Jurnal Serambi Engineering, 2022)
Basically the road will experience a decrease in structural function in proportion to the increasing age of the pavement. Road damage is currently a controversial issue, where some say that the pavement damage is caused because the highway is designed with a substandard quality level, and on the other hand it is stated that the pavement damage is caused by overload vehicles crossing the road that way.This research was conducted for 1 week (23 May 2022 – 29 May 2022) this research was conducted at 07.00 – 22.00 WIB (15 hours) on Mahir-Mahar road in the city of Palangka Raya. The results of the analysis show that 9,67 % of the area of Mahir-Mahar road in the city of Palangka Raya is damaged, with 5.10 % of road damage caused by overloaded vehicles. From the analysis of the remaining life of the road plan (remaining life) on Mahir-Mahar road the direction of the RTA Milono road to net Tjilik Riwut km 10 road for the next 10 years it has a remaining life of 48.42% and Mahir-Mahar road from Tjilik Riwut km 10 road to net RTA Milono road for the next 10 years, has a remaining life of 52.22%.Kata kunci : overload, road damage, remaining road design life.